HUMAN RESOURCE MANAGEMENT IN LIBRARIES: RECRUITMENT AND RETENTION STRATEGIES - Jagmohan Meena (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Human Resource Management (HRM) in libraries plays a crucial role in ensuring the effective functioning of library services by recruiting and retaining skilled professionals. This study explores the recruitment and retention strategies adopted by libraries to enhance their workforce. With the ever-evolving demands in the field of librarianship, challenges such as skill gaps, technological advancements, and employee turnover require a strategic approach. This research aims to analyze current HRM practices in libraries, identify key strategies for recruitment and retention, and provide recommendations for improving HRM in academic and public libraries.